Latin America and the Caribbean on the road to Rio+20* (ECLAC SantiagoCL, 2011)
Reviews and assesses the time period 1992 - 2010 in Latin America and the Caribbean since the end of the Earth Summit in 1992. Sets out the guidelines for a sustainable development strategy for the region based on a holistic vision of the social, economic and environmental pillars.
Revision of the document "Inputs for the Governments of Latin America and the Caribbean for formulating a regional stance for the Rio+20, presented at the Latin American and Caribbean Regional Meeting Preparatory to the United Nations Conference on Sustainable Development, Santiago, 7-9 December 2011.